Standardization of a procedure for candied langka (Athocarpus Integra L.) - Asistido, Eva C. (1981)
ABSTRACT The study dealt with the determination of the optimum processing conditions for candied langka. This involved the standardization of a laboratory procedure for candying, its translation into pilot-scale production and evaluation of the products for their moisture content, soluble solids,pH and tritable acidity as well as their sensory qualities and product cost. Candied langka of highly acceptable quality characteristics- free from sugar crystals. bright to golden yellow in color, firm to chewy in texture with a distinct langka flavor, can be produced by using the step-up method of syruping with 35 Brix as the starting syrup concentration and 65 Brix as the final concentration level. The concentration of the syrup may be increased to 65 Brix by increments of 10, 20 or 30 Brix, although the step-up by 30 Brix proved to be the least time consuming. To prevent browning discolorations during processing and storage, the langka bulbs were blanched for 3 minutes in live steam prior to syruping and Na₂S₂0₅ in the amount of 0.1% by weight of syrup was added to the initial 35 Brix syrup. After syruping, the fruits were dried in forced draft cabinet dryer at 54-60°C (130-140 F) to a final moisture content of 16-20%. Translation of the standardized laboratory procedure into pilot-scale production proved to be feasible without altering the physico-chemical properties, quality characteristics and general acceptability of the product. Moreover, it proved to be a way of reducing production cost.